Analisis Semiotika Konflik Ideologi (Analisis Sosiologi Media Pada Film Jenderal Soedirman) - Rudolof Ngalu; Lasarus Jehamat; Laurensius D.E.P. Putra (Jurnal Pendidikan dan Kebudayaan Missio, 2020)
This research is entitled Semiotic Analysis of Ideology Conflict (Media Analysis of Sociology in General Soedirman's Film). This research is based on the consideration that all things including films are not immune to the process and power relations. The presence of a film has a purpose and therefore has a certain meaning. This research focuses on the analysis of interarideological conflicts in the film General Soedirman. It is said, in the film, conflicts often occur in several segments. All conflicts are certainly based on certain roots and causes. Likewise, every conflict always has a certain dynamic. Whatever the reason, the dynamics of the conflict whether socially or symbolically in the film has a certain meaning. Therefore, the dynamics of the conflict can be analyzed and worth checking. The study uses Ralf Dahrendorf's conflict theory. The analysis of this study uses a qualitative interpretive concept. The method used as an analytical machine uses the Roland Barthes semiotics method. Roland Barthes' semiotics focuses the analysis of signs by looking at denotations, connotations and myths. The results showed a number of ideological conflicts that occurred in the film. Some of them are conflicts between narrow ideology of nationalism (chauvinism) vs. fascism, between nationalism vs. colonialism, between nationalism vs. communism, and communism vs. colonialism conflict. Understanding of ideological conflicts is urgently analyzed so that people are not manipulated by various ideas and ideas that emerge from certain regimes can be immediately overcome.